Dietary digestible lysine requirement and essential amino acid to lysine ratio for pacu Piaractus mesopotamicus - Abimorad, Eduardo Gianini [UNESP]; Favero, G. C. [UNESP]; Squassoni, G. H. [UNESP]; Carneiro, D. [UNESP] (Wiley-Blackwell, 2010)
To determine the digestible lysine requirement for pacu juveniles, a dose-response feeding trial was carried out. The fish (8.66 +/- 1.13 g) were fed six diets containing the digestible lysine levels: 6.8, 9.1, 11.4, 13.2, 16.1 and 19.6 g kg-1 dry diet. The gradual increase of dietary digestible lysine levels from 6.8 to 13.2 g kg-1 did not influence the average values of the parameters evaluated (P > 0.05). The increase of dietary digestible lysine level to 16.1 g kg-1 significantly improved weight gain (WG), specific growth rate (SGR), protein productive value (PPV), protein efficiency rate (PER), and apparent feed conversion rate (FCR), but was not different from fish fed diets containing 19.6 g kg-1 lysine. Fish fed diets containing 16.1 and 19.6 g kg-1 digestible lysine showed lower body lipid contents than fish in the other treatments. The digestible lysine requirement as determined by the broken-line model, based on average WG values, was 16.4 g kg-1. The other essential amino acid requirements were estimated based on the ideal protein concept and the value determined for lysine.
Keywords: body composition; digestibility; ideal protein; l-lysine; Piaractus mesopotamicus; white muscle